THE EFFECT OF TAX DIGITALIZATION ON TAX COMPLIANCE: A LITERATURE REVIEW STUDY - Olivia Putri Zahrani; Rafi Fadhlurrahman; Luk Luk Fuadah (LP2M IBK Nitro, 2026)
This study aims to provide a summary of tax compliance. Using a systematic literature review (SLR) method, this study focuses on examining how tax digitalization affects tax compliance. This literature review focused on 25 journal articles, consisting of articles indexed by Scopus. The findings indicate that the theory of planned behavior is the most commonly used theory in research on tax digitalization and tax compliance. Based on the literature review conducted by the researcher, previous research on the relationship between tax digitalization and tax compliance has yielded inconsistent results. This is due to various factors such as the research period, sample size, and the theory used..